Numerical Simulation of the Thermal Performance of a Tubular Solar Air Heater (Journal of Engineering, 2023)
In this work, a flat-plate solar air heater (FSAH) and a tubular solar air heater (TSAH) were designed and tested numerically. The work investigates the effect of increasing the contact area between the flowing air and the absorber surface of each heater and predicts the expected results before the fabrication of the experimental rig. Three-dimensional two models were designed and simulated by the ANSYS-FLUENT 16 Program. The solar irradiation and ambient air temperature were measured experimentally on December 1st 2022, at the weather conditions of Baghdad City- Iraq, at three air mass flow rates, 0.012 kg/s, 0.032 kg/s, and 0.052 kg/s. The numerical results showed the advantage in the thermal performance of the TSAH in comparison to the FSAH, represented by better air temperature difference, better heat transfer from the absorber to air, and better thermal efficiency. The TSAH has a higher thermal efficiency than the FSAH by 7 %, 19 % °C, and 22 % at 0.012 kg/s, 0.032 kg/s, and 0.052 kg/s, respectively. The improvement of the thermal characteristics of the TSAH can be referred to as the increment in the heat transfer contact area between the absorber and the flowing air.